Employment preferences of obstetricians and gynecologists to work in the district hospitals: evidence from a discrete choice experiment in Nepal - Bishnu Gautam; Vishnu Prasad Sapkota; Rajendra Raj Wagle (BMC, 2019)
Abstract Background A mismatch between the requirement and annual production of obstetricians and gynecologists (OBs-GYNs) was observed in Nepal. On top of that, recruitment and retention of OBs-GYNs is a pressing problem, especially in district hospitals of Nepal. In this connection, evidence on the job priorities and preferences of OBs-GYNs, which is currently lacking in Nepal, would help in policymakers in devising recruitment and retention strategies in these hospitals. This study, therefore, aims at exploring the most relevant job attributes that OBs-GYNs would prefer to work in the district hospitals of Nepal using a discrete choice experiment (DCE) technique. Methods Job attributes relevant to design the questionnaire were identified using keyinformant interviews and focusgroup discussions with policymakers and top managers. Then, 48 choice sets were developed using a fractional factorial design. Using these unlabeled choice sets, a DCE was conducted among 189 OBs-GYNs. The multinomial logistic regression model was used to estimate the marginal utilities and other model parameters. The willingness to pay/accept estimates was also measured for each job attribute. Results OBs-GYNs preferred the presence of a full team at the workplace (OB-GYN, pediatrician, and anesthesiologist), provision of primary and secondary education for children, and opportunity of private practice. On the other hand, a few job attributes such as a higher duration of service in district hospitalsand the provisions of a car allowance were preferred less by the respondents. Results from the marginal utility by the OBs-GYNs would be open to trade among the attributes. Conclusions The job attributes identified as incentives in this study should be included in a package to attract OBs-GYNs to serve in district hospitals of Nepal rather than offering a standard incentive package to all health workers. Similarly, this study confirmed the importance of the combination of non-monetary and monetary interventions in attracting and retaining health workers in district hospitals of Nepal.